2021
DOI: 10.1186/s12884-021-03895-2
|View full text |Cite
|
Sign up to set email alerts
|

The views of postnatal women and midwives on midwives providing contraceptive advice and methods: a mixed method concurrent study

Abstract: Background Provision of contraception to women in the immediate postnatal period has been endorsed by professional bodies, to reduce the incidence of short inter-pregnancy intervals. This study examined the views of postnatal women and practising midwives regarding provision of contraceptive advice and contraceptive methods by midwives, in a region of the United Kingdom. Methods A mixed-method approach using qualitative interviews with midwives, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 30 publications
2
33
0
Order By: Relevance
“…The midwives in our study told us that they want to work to the full scope of their practice and provide holistic care 24. National and international studies have found women want midwives to offer expert care across their pregnancy journey 25 26. Postpartum contraception advice from midwives, for example, was well received by women in a UK study in which women cited trust and continuity of care as contributing factors 25.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The midwives in our study told us that they want to work to the full scope of their practice and provide holistic care 24. National and international studies have found women want midwives to offer expert care across their pregnancy journey 25 26. Postpartum contraception advice from midwives, for example, was well received by women in a UK study in which women cited trust and continuity of care as contributing factors 25.…”
Section: Discussionmentioning
confidence: 86%
“…National and international studies have found women want midwives to offer expert care across their pregnancy journey 25 26. Postpartum contraception advice from midwives, for example, was well received by women in a UK study in which women cited trust and continuity of care as contributing factors 25. Dutch midwives are already providing unstructured preconception counselling 27.…”
Section: Discussionmentioning
confidence: 99%
“…16 Promoting consultations about contraception with midwives outside the perinatal period could be another option. 17 Lastly, training other health professionals, such as nurses, on the insertion of IUDs is a possibility that should be considered. 18 In the present study, women who had a pregnancy history in the year before dispensation of a device were more likely to get a Cu-IUD rather than a LNG-IUS.…”
Section: Discussionmentioning
confidence: 99%
“…The financial incentive for general practitioners to insert an IUD could be a lever to promote dispensation of Cu‐IUD/LNG‐IUS and to decrease unequal access to long‐acting reversible contraception as observed in the United Kingdom 16 . Promoting consultations about contraception with midwives outside the perinatal period could be another option 17 . Lastly, training other health professionals, such as nurses, on the insertion of IUDs is a possibility that should be considered 18 …”
Section: Discussionmentioning
confidence: 99%
“…47 48 Both nurses and midwives are generally supportive of such an expanded role within their scope of practice, 5 49 50 as occurs in other international settings. 40 41 51 52 Exploration of nurse- and midwifery-led models of contraceptive care in Australia will therefore be critical to increasing access to effective contraception. 38 39 53…”
Section: The Opportunities: Strategies For Increasing Access To Contr...mentioning
confidence: 99%